Jordan National Security in the Age of Uncertainty - Amani G. Jarrar (RIRAI Publisher, 2026)
This paper discusses Jordan national security in the age of uncertainty. It reflects on the concept of national security that has undergone a profound transformation in recent decades, moving beyond its traditional association with military defense and territorial integrity toward a more comprehensive and multidimensional understanding. Jordan’s national security experience illustrates how wise leadership, grounded in legitimacy, pragmatism, and long-term vision, can guide a state toward safety amid uncertainty, making governance itself a core pillar of national security rather than a peripheral factor. This paper analyzes six dimensions: Reconceptualizing security in an era of uncertainty, moving from traditional security to human-centered security, defining types and pillars of national security, in terms of political security, economic security, social security, and highlighting institutional and governance pillars, systemic interaction, based on security, stability, and strategic governance, discussing managing national security under continuous uncertainty, and finally reading in depth national security from both the classical strategic thought and contemporary Jordanian Practice. The study concludes with reframing national security through soft security concerns, reaching key recommendations, such as: Institutionalizing soft security within national security frameworks, strengthening governance and policy coordination mechanisms, prioritizing preventive diplomacy and confidence-building measures, linking economic and social development to security planning, and finally enhancing societal resilience and national cohesion.